The imperative to build research capacity and promote evidencebased practice in Australian perioperative nurses - Jed Duff (Journal of Perioperative Nursing)
Evidence-based practice is considered the gold standard of care, and as such it is now an expectation of our patients, regulatory agencies and health care funders. Unfortunately, much of what we do in perioperative nursing continues to be based on tradition and history rather than robust clinical evidence. Even when evidence is available to use, it is often not fully applied in practice. If we want to maintain our standing as a leading nursing specialty, then we need to address this issue by engaging with research and growing our evidence base. To do this, we need to conduct and disseminate rigorous primary research, clinically relevant systematic reviews and evidence-based practice projects.